DOES DEMOGRAPHICS HAS AN ASSOCIATION WITH USAGE PATTERNS AND LEVEL OF SATISFACTION TOWARDS PUBLIC TRANSPORT SYSTEMS: A CASE OF METRO CHENNAI RAIL - Appu, Mr.A.; Balaji, Dr.S.G. (The journal of contemporary issues in business and government, 2021)
Personal demographics play a role in the usage and satisfaction of metro rail. It may be due to the level of awareness, and the usage interest has a close association with the earnings and age. Gender helps free movement of people without time frame and constraints. Hence, modern transport systems usage has a moderate level of association with the personal and social demographics of the commuters is observed in the study. For the survey, three divisions of metro rail are taken up, and the sample size of 683 is arrived at using the scientific method. The present research is descriptive, and the data collection tools are prepared and tested with reliability alpha and found it as 0.896 and found reliable. The results observed that gender, lifestyle, and occupation significantly affect the usage and satisfaction towards metro rail in the sample. On the other hand, age, level of income, frequency of travel has no association with the level of usage and satisfaction.